Priority Management of Nature Tourism in Sirah Kencong Tourism Area Blitar East Java-Indonesia - Sani, Fitria Earlike Anwar; Budiarsa, Made; Paturusi, Syamsul Alam; Lanya, Indayati (International Journal of Psychosocial Rehabilitation, 2020)
At this time, the Indonesian government is developing one of the country’s foreign exchange sources. Blitar is one of the districts included in the National Tourism Development Zone and the National Nature Tourism Development Program. In fact, the Sirah Kencong Tourism Area in Blitar is among the ten best natural attractions in East Java, Indonesia. The purpose of this study is to select a priority management model to improve tourist attractions in Sirah Kencong Tourism Area. The method used in this study is the Analytical Hierarchy Process (AHP). This study uses ten criteria and four alternatives for assessment by ten experts working in the local government sector, the private sector and the community. The results in this study prove that the model designed to increase tourist attractiveness in the Sirah Kencong Tourism Area is the Destination Management Organization (DMO) model. Destination Management Organization (DMO) is a professional manager that has members of the stakeholders consisting of local governments, the private sector and the community who support the improvement of tourism, safety security and provide a positive image on attractions.